Neoadjuvant radiochemotherapy significantly alters the phenotype of plasmacytoid dendritic cells and 6-sulfo LacNAc+ monocytes in rectal cancer - Wagner, Felix; Reißfelder, Christoph; Schäkel, Knut (Frontiers in immunology, 2019)
Neoadjuvant radiochemotherapy (nRCT) can significantly influence the tumor immune architecture that plays a pivotal role in regulating tumor growth. Whereas various studies have investigated the effect of nRCT on tumor-infiltrating T cells, little is known about its impact on the frequency and activation status of human dendritic cells (DCs). Plasmacytoid DCs (pDCs) essentially contribute to the regulation of innate and adaptive immunity and may profoundly influence tumor progression. Recent studies have revealed that higher pDC numbers are associated with poor prognosis in cancer patients. 6-sulfo LacNAc-expressing monocytes (slanMo) represent a particular proinflammatory subset of human non-classical blood monocytes that can differentiate into DCs. Recently, we have reported that activated slanMo produce various proinflammatory cytokines and efficiently stimulate natural killer cells and T lymphocytes. slanMo were also shown to accumulate in clear cell renal cell carcinoma and in metastatic lymph nodes from cancer patients. Here, we investigated the influence of nRCT on the frequency of rectal cancer-infiltrating pDCs and slanMo. When evaluating rectal cancer tissues obtained from patients after nRCT, a significantly higher density of pDCs in comparison to pre-nRCT tissue samples was found. In contrast, the density of slanMo was not significantly altered by nRCT. Further studies revealed that nRCT significantly enhances the proportion of rectal cancer-infiltrating CD8+ T cells expressing the cytotoxic effector molecule granzyme B. When exploring the impact of nRCT on the phenotype of rectal cancer-infiltrating pDCs and slanMo, we observed that nRCT markedly enhances the percentage of inducible nitric oxide synthase- or tumor necrosis factor alpha-producing slanMo. Furthermore, nRCT significantly increased the percentage of mature CD83+ pDCs in rectal cancer tissues. Moreover, the proportion of pDCs locally expressing interferon-alpha, which plays a major role in antitumor immunity, was significantly higher in post-nRCT tissues compared to pre-nRCT tumor specimens. These novel findings indicate that nRCT significantly influences the frequency and/or phenotype of pDCs, slanMo, and CD8+ T cells, which may influence the clinical response of rectal cancer patients to nRCT.
Gesehen am 22.05.2019